Diet and disease in modern society - Harding, Ben; Video Education Australasia (Australia : Video Education Australasia, 2002)
This program look at the relationship between diet and disease, examining in detail the way foods both protect against and contribute to the most significant disease or our age, the intearction with other health influences and the recent signal government health initiative that will shape our health for decades to come
Title from title screen
Executive producer, Mark Auliffe ; graphics, Reece Sanders ; editor, Michael Henry ; camera Simon Wright
Presenter: Andrea Waycott
Keywords: Nutritionally induced diseases; Nutrition; Diet; Diet therapy